2019
DOI: 10.1017/s0022215119001816
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of factors affecting choice of otolaryngology as a career in medical students and junior doctors

Abstract: BackgroundThere is growing concern over a future shortfall in provision of UK otolaryngology consultants. There is a declining rate of applications to otolaryngology specialty training in the UK.ObjectiveThis study aimed to systematically review the literature to establish what factors influence medical students’ and junior doctors’ decision to pursue a career in otolaryngology.MethodMedline, Embase and PubMed databases were searched in January 2019. Additional manual reference checks of identified literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…[4][5][6] A lack of consistency across UK medical schools with regard to their undergraduate ENT curriculum further compounds these shortcomings, 7 which is concerning as this stage of training is crucial in encouraging students to pursue a career in ENT. 8 Furthermore, it was found that 30 per cent of general practitioners in South West England had received no formal hospital experience or had any form of post-graduate teaching in ENT. 9 In conjunction with this, anatomy should form an integral part of any surgical education, yet only 53.8 per cent of newly qualified doctors felt they had received adequate anatomy teaching in medical school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] A lack of consistency across UK medical schools with regard to their undergraduate ENT curriculum further compounds these shortcomings, 7 which is concerning as this stage of training is crucial in encouraging students to pursue a career in ENT. 8 Furthermore, it was found that 30 per cent of general practitioners in South West England had received no formal hospital experience or had any form of post-graduate teaching in ENT. 9 In conjunction with this, anatomy should form an integral part of any surgical education, yet only 53.8 per cent of newly qualified doctors felt they had received adequate anatomy teaching in medical school.…”
Section: Introductionmentioning
confidence: 99%
“… 4 6 A lack of consistency across UK medical schools with regard to their undergraduate ENT curriculum further compounds these shortcomings, 7 which is concerning as this stage of training is crucial in encouraging students to pursue a career in ENT. 8 Furthermore, it was found that 30 per cent of general practitioners in South West England had received no formal hospital experience or had any form of post-graduate teaching in ENT. 9 …”
Section: Introductionmentioning
confidence: 99%
“…3 In this month's issue of the Journal of Laryngology & Otology, Mayer et al make a strong case for greater exposure to ENT within the medical school curriculum, in order to facilitate active recruitment of medical students and junior doctors into Otolaryngology Higher Surgical Training. 4 The authors also encourage mentorship for students with an interest in ENT.…”
mentioning
confidence: 97%